2011
DOI: 10.5603/fhc.2011.0023
|View full text |Cite
|
Sign up to set email alerts
|

Peptide vaccination induces profound changes in the immune system in patients with B-cell chronic lymphocytic leukemia

Abstract: Abstract:Although the immune status of chronic lymphocytic leukemia (CLL) patients is mostly characterized by immunosuppression, there is an accumulation of in vivo (graft-versus-leukemia effect) and in vitro (spontaneous remissions after infections) data that indicates that CLL might be effectively targeted by T-cell based immunotherapy. Recently, we characterized receptor for hyaluronic acid mediated motility (RHAMM) as a preferential target for immunotherapy of CLL. We also completed a RHAMM-derived peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In contrast to solid tumors, little is known about the immunobiology of Th17 cells in hematologic malignancies, particularly CLL [90]. Initial studies about the IL-17 producing T cells in CLL were recently performed in a limited sample size and showed highly variable results [91][92][93]. Following these observations, we showed that the frequencies of both Th17 and Tc17 cells were markedly decreased in CLL patients and correlated with disease progression.…”
Section: Th17 Cells In Cllmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast to solid tumors, little is known about the immunobiology of Th17 cells in hematologic malignancies, particularly CLL [90]. Initial studies about the IL-17 producing T cells in CLL were recently performed in a limited sample size and showed highly variable results [91][92][93]. Following these observations, we showed that the frequencies of both Th17 and Tc17 cells were markedly decreased in CLL patients and correlated with disease progression.…”
Section: Th17 Cells In Cllmentioning
confidence: 79%
“…The frequency of Th17 cells was about 3% of the total CD4 + T cells in a limited number of CLL/SLL patients [91] The highly variable number of IL-17 producing CD4 + and CD8 + T cells [92,93] Decreased frequencies of both Th17 and Tc17 cells which was correlated with disease progression [94] Increased frequency of IL-17 producing follicular Th cells which was correlated with advanced CLL stages [95] Treatment of CLL patients with lenalidomide led to induction of Th17 cells [93] Increased frequency of IL-17 producing T cells in CLL/SLL patients compared with other B cell malignancies [91] Increased frequency of Th17 cells was correlated with better prognostic markers and longer survival The microenvironmental milieu in leukemic spleens enhances the recruitment and expansion of Th17 and other IL-17-expressing cells [97] Decreased Th17 and IL-17A levels which were correlated with progressive disease IL-17A inversely correlated with the time from CLL diagnosis to the start of therapy [98] CLL/SLL: Chronic lymphocytic leukemia/small lymphocytic lymphoma; IL: Interleukin; Th: T helper. [94].…”
Section: Main Claimmentioning
confidence: 99%
“…Indeed, spectrometric studies on the naturally presented HLA ligands in CLL identified a pool of antigens exclusively expressed in CLL patients, providing information regarding the immunogenicity of the malignant cells while also offering new treatment targets ( 107 ). However, clinical studies targeting neoepitopes expressed in the malignant cells demonstrate enhanced rejection of tumor cells, underling the safety profile of these approaches ( 124 , 125 ).…”
Section: Treatment Options In Cll and Implication Of The T Cell Compamentioning
confidence: 99%
“…The vaccine had similar immunological (i.e., increase in R3-specific CD8+ cells) and clinical response in patients with chronic lymphocytic leukemia (Giannopoulos et al, 2010). Interestingly, although patients with CML are characterized as having immunosuppression, the vaccine caused profound changes (mostly an increase) in different T cell subsets and in cytokines that are involved in immune response (i.e., TGF-β, IL-10, IL-2, and TNF) during the vaccination period (Giannopoulos, Wlasiuk, Dmoszynska, Rolinski, & Schmitt, 2011). However, despite the early success with the R3-peptide vaccine, it was recently shown that only baseline RHAMM expression was present in both leukemic stem cells (CD34+CD38−) and hematopoietic stem cells (CD34+CD38−) from healthy control cells.…”
Section: Targeting Ha Receptorsmentioning
confidence: 99%